SZ_GERICHTE BEK 2017 198 vom 12. März 2018 , Ausstand, amtliche Verteidigung, Akteneinsicht, Teilnahmerecht - SZ Gerichte (2018)
Ausstand, amtliche Verteidigung, Akteneinsicht, Teilnahmerecht | Strafgesetzbuch